2009
DOI: 10.1080/08927010902853516
|View full text |Cite
|
Sign up to set email alerts
|

Mini-review: quorum sensing in the marine environment and its relationship to biofouling

Abstract: Bacterial quorum sensing (QS) is a cell-cell communication and gene regulatory mechanism that allows bacteria to coordinate swarming, biofilm formation, stress resistance, and production of toxins and secondary metabolites in response to threshold concentrations of QS signals that accumulate within a diffusion-limited environment. This review focuses on the role of QS signaling and QS inhibition in marine bacteria by compounds derived from marine organisms. Since the formation of a biofilm is considered to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
262
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(265 citation statements)
references
References 119 publications
1
262
0
2
Order By: Relevance
“…The ability to manipulate QS in associated microbiota is a common trait of marine organisms (Dobretsov et al, 2009). Therefore, it is, perhaps, not surprising that one of the most abundant cyanobacterial metabolites within BBD is a compound capable of manipulating QS in Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to manipulate QS in associated microbiota is a common trait of marine organisms (Dobretsov et al, 2009). Therefore, it is, perhaps, not surprising that one of the most abundant cyanobacterial metabolites within BBD is a compound capable of manipulating QS in Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…form highly connected hubs in the cluster representing stable microbiome (Supplementary Figure S6). Cross-species manipulation of QS is a wellcharacterized mechanism of microbe-microbe interactions with community-wide consequences (Dobretsov et al, 2009;Teplitski et al, 2011). Therefore, lyngbic acid extracted from BBD was subjected to a series of bioassays to elucidate its effect on QS in Vibrio spp.…”
Section: Lyngbic Acid Inhibits Cqss-mediated Qs In Vibrio Sppmentioning
confidence: 99%
“…Many literatures reported that marine biofilm might secrete chemical cues to attract invertebrate larvae and macro-algal spores and enhance the settlement of larvae and spores (Joint et al, 2002;Dobretsov et al, 2009;Tait and Havenhand, 2013). So it is very important to inhibit the growth of bacteria and diatom for controlling marine biofouling.…”
Section: Introductionmentioning
confidence: 99%
“…Production of QS signals has also been reported in cultures of coral-associated vibrios, although the role of QS in coral diseases caused by these microorganisms has not yet been established (Tait et al, 2010). Because QS has important roles in the interactions within microbial communities, various forms of QS manipulation have been documented (Givskov et al, 1996;Pasmore and Costerton, 2003;Skindersoe et al, 2008;Dobretsov et al, 2009). How these interactions carry out in natural habitats is far from being clear.…”
Section: Introductionmentioning
confidence: 99%